Organic nutrient management of papaya (Carica papaya L.) - Divya Hari (Department of Pomology and Floriculture, College of Agriculture, 2018)
The present study entitled “Organic nutrient management in papaya (Carica papaya L.)” was carried out in the Department of Pomology and Floriculture, College of Agriculture, Vellayani during 2016-2018, with an objective to study the effect of organic nutrient management on growth, yield and quality of papaya. The experiment was conducted in RBD with 11 treatments and 3 replications using papaya variety Surya. The treatments included in the study are: T1-100% of recommended dose of N as organic, T2-75% of recommended dose of N as organic, T3-100% of recommended dose of N as organic + PGPR Mix-I, T4-75 % of recommended dose of N as organic + PGPR Mix-I, T5-100% of recommended dose of N as organic + AMF , T6-75% of recommended dose of N as organic + AMF, T7-100% of recommended dose of N as organic + PGPR Mix-I+ AMF , T8-75% of recommended dose of N as organic + PGPR Mix-I+ AMF, T9-Full NPK of KAU POP + Vermicompost (N equivalent to FYM of KAU POP), T10- 100% RDF (240:240:480 g NPK plant-1 year-1, FYM-10 kg plant-1 year-1 ) , T11- Absolute control. The present study revealed that, application of 100% of recommended dose of N as organic along with PGPR Mix-I and AMF increased the girth of the plant, number of leaves, fruit set percentage with lowest height for first flowering and reduced the number of days for flowering. The highest plant height was obtained by the application of 75% of recommended dose of N as organic along with AMF. With regard to the yield characters studied, highest fruit weight, fruit length, fruit girth, fruit volume, pulp percentage, flesh thickness, total yield plant-1 (39.91 kg plant-1) and minimum number of days for maturity were recorded by the application of 100% of recommended dose of N as organic along with PGPR Mix-I and AMF. Number of fruits plant-1 was found to be highest with application of 100% RDF (240:240:480 g NPK plant-1 year-1, FYM-10 kg plant-1 year-1). The study on quality parameters of fruit revealed that TSS, ascorbic acid, carotenoids, total sugar, reducing sugar and the organoleptic qualities were highest with the application of 100% of recommended dose of N as organic along with PGPR Mix-I and AMF. Analysis of soil nutrient status revealed that soil organic carbon, soil EC, nitrogen and potassium content were highest with the application of 75% recommended dose of N as organic along with AMF. Phosphorus, micronutrient content and microbial count were highest with the application of 100% recommended dose of N as organic along with AMF. The leaf petiole analysis of papaya indicated that the highest phosphorus, potassium and micronutrient content increased with the application of 100% of recommended dose of N as organic along with PGPR Mix-I and AMF. Regarding the B: C ratio and net income obtained, application of 100% of recommended dose of N as organic along with PGPR Mix-I and AMF recorded the highest. Overall assessment indicated that application of 100% of recommended dose of N as organic along with PGPR Mix-I and AMF in 6 splits at bimonthly interval improved the growth, yield, quality of papaya.